Implementation of Electronic Land Service System on the Effectiveness of Land Deed Officials in South Jakarta - Alifa, Alifa; Sudiro, Ahmad (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The development of information technology in the land sector has encouraged the birth of a digitalization policy for services by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) through the implementation of the Electronic Land Service System. This innovation is intended to increase transparency, speed, and accuracy in the land administration process, especially for Land Deed Officials (PPAT) who are at the forefront of land rights transfer services. This study aims to examine the influence of the Electronic Land Service System on the effectiveness of PPAT work in the South Jakarta Administrative City area. The study uses an empirical approach with quantitative and qualitative methods, where data is obtained through distributing questionnaires and interviews with active PPATs. The results of the analysis show that the implementation of the Electronic Land Service System has a positive impact on work time efficiency, document accuracy, and increased service satisfaction. However, a number of obstacles were still found, such as lack of technical training and limited system accessibility under certain conditions. Based on these findings, optimization of digital infrastructure and increased user capacity are needed so that the Electronic Land Service System can run more optimally and sustainably in supporting PPAT performance and quality public services.